The Impact of Combine Level of Capital Structure and Dividend Policy on Firm Stock Price An apply study of companies listed on Amman Stock Exchange - مجيد, ارشد فؤاد; ابو سمرة, وفاء حسين (Journal of Economics and Administrative Sciences, 2015)
Although a great deal of works has been done on the area of capital structure and dividend policy, there is still insufficient knowledge of how these policies affect stock prices. This shortcoming may have been originated from the separation between both policies when investigating their effect on stock prices. Based on this point, this research adopts a new technique (completely randomized design), to combine the effect of capital structure and dividend policy on stock prices rather than separating between them. The study used panel based regression analysis depending on the sample of 30 service and industrial Jordanian firms for the period of 2001-2010. The result of test hypotheses found the following; 1) dividend payout has a positive effect on firm stock prices. 2) Firm leverage has a negative effect on firm stock prices. 3) Combined level of capital structure and dividend policy has an effect on stock prices. 4) Different levels of combined level of capital structure and dividend policy affect stock prices in a different way